Recreational sports in prison: inmates' perspectives on coaching effectiveness - Dransmann, Milan; Lesch, Lara; Gröben, Bernd; Wicker, Pamela (Frontiers in Sports and Active Living, 2024)
Introduction This study examines inmates' perspectives on the effectiveness of sports coaches in prison. According to the integrative definition of effective coaching, coaches require professional, interpersonal, and intrapersonal knowledge to enhance athletes' outcomes within a specific context. Methods Five male inmates of a German prison were interviewed after they participated in sports programs. The data were analyzed using directed content analysis. Results The inmates recognized professional knowledge in coaches who demonstrated clear training structures and spoke in an educated manner. Interpersonal knowledge was highly valued, with inmates expressing a preference for coaches who showed closeness, truthfulness, and responsiveness, while intrapersonal knowledge was attributed through coaches' adaptability. Inmates identified all four possible outcomes and emphasized that sensitivity, authenticity, energetic demeanor, physical appearance, and athletic skills are crucial qualities for an effective coach in a prison. Discussion The balance between an authentic and energetic demeanor, including a certain degree of strictness, emerges as a key factor in effective coaching within the prison context.